Conformity Analysis of HOTS (Higher-order Thinking Skills) Based on Critical Thinking in the Evaluation of High School Biology Learning in the East Cirebon Region - Mudaningrat, Ajeng; Maryuningsih, Yuyun; Anugrah, Indah Rizki (Biosfer: Jurnal Tadris Biologi, 2022)
This study aims to analyze the suitability of HOTS (Higher-order Thinking Skills) based on critical thinking on the Odd Semester Final Examination questions for high school biology lessons in the East Cirebon Region. The research subjects were schools in the Cirebon area, namely SMAN 1 Lemahabang, MAN 3 Buntet Pesantren Cirebon and MA NU Putri Buntet Pesantren Cirebon. Data analysis is presented in the form of percentages and then described based on critical thinking indicators (characteristic thinking) based on Facione, (2011) on the Biology Final Semester Exam (UAS). The odd semester final exam (UAS) for biology subjects already contains critical thinking skills, but the percentage is still low. The most dominating indicator is interpretation. Based on this research, it shows that the questions made by the teacher are not sufficient to cultivate students' critical thinking skillsABSTRAK: Penelitian ini bertujuan untuk menganalisis kesesuaian HOTS (Higher-order Thinking Skills) berdasarkan critical thinking pada soal Ujian Akhir Semester ganjil pelajaran biologi SMA se-Wilayah Cirebon Timur. Subjek penelitian adalah sekolah yang ada di wilayah Cirebon yaitu SMAN 1 Lemahabang, MAN 3 Buntet Pesantren Cirebon dan MA NU Putri Buntet Pesantren Cirebon. Analisis data disajikan dalam bentuk persentase selanjutnya dideskripsikan berdasarkan indikator berpikir kritis (ciritical thinking) berdasarkan Facione, (2011) pada soal Ujian Akhir Semester (UAS) biologi. Ujian Akhir Semester (UAS) ganjil mata pelajaran biologi sudah memuat keterampilan berpikir kritis, namun dengan persentase yang masih rendah. Indikator yang paling mendominasi adalah interpretasiBerdasarkan penelitian tersebut menunjukkan bahwa soal yang dibuat oleh guru belum memadai untuk menumbuhkan keterampilan berpikir kritis siswa